2020
DOI: 10.3390/md18110552
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization and Bioactive Properties of Alkali-Extracted Polysaccharides from Enteromorpha prolifera

Abstract: Four new purified polysaccharides (PAP) were isolated and purified from the Enteromorpha prolifera by alkali extraction, and further characterization was investigated. Their average molecular weights of PAP-1, PAP-2, PAP-3, and PAP-4 were estimated as 3.44 × 104, 6.42 × 104, 1.20 × 105, and 4.82 × 104 Da, respectively. The results from monosaccharide analysis indicated that PAP-1, PAP-2, PAP-3 were acidic polysaccharides and PAP-4 was a neutral polysaccharide. PAP-1 and PAP-2 mainly consist of galacturonic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In addition, the concentration of elution solvent affects the monosaccharide composition and content. Recently, Zhao et al (26) extracted crude polysaccharide from E. prolifera using the alkali method and fractionated it by stepwise elution with 0 (AP-1), 0.3 (AP-2), 0.5 (AP-3), 0.7 (AP-4) M NaCl solution through an anion-exchange column. The monosaccharide analysis indicated that PAP-1 and PAP-2 mainly consist of galacturonic acid, while PAP-3 and PAP-4 mainly contained rhamnose.…”
Section: Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the concentration of elution solvent affects the monosaccharide composition and content. Recently, Zhao et al (26) extracted crude polysaccharide from E. prolifera using the alkali method and fractionated it by stepwise elution with 0 (AP-1), 0.3 (AP-2), 0.5 (AP-3), 0.7 (AP-4) M NaCl solution through an anion-exchange column. The monosaccharide analysis indicated that PAP-1 and PAP-2 mainly consist of galacturonic acid, while PAP-3 and PAP-4 mainly contained rhamnose.…”
Section: Extraction Methodsmentioning
confidence: 99%
“…E. prolifera polysaccharides have been increasingly investigated for their role in the functional food and pharmaceutical industry (26). For example, Enteromorpha species was used as an ingredient in the preparation of pakoda, a common traditional snack food in India (27).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported in other studies (Ao & Kim, 2020; Guo et al, 2021; Ming et al, 2009). The enhancement of antioxidant activity may be related to plant polysaccharide characteristics, such as molecular weight, monosaccharide composition, and spatial structure (M. Zhang, Wang et al, 2014; Zhao et al, 2020). In addition, the components of polysaccharides also have an impact on antioxidant capacity (L. Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…From a nutritional standpoint, the main properties of sea lettuce are its richness in polysaccharides, protein and Amino acids, Fatty acids, Minerals and Vitamins. Therefore, their nutritional value makes them valuable food supplements 36,37 .…”
Section: Medicinal Properties Of Enteromorphamentioning
confidence: 99%